СВЧ – техника при измерении влажности семян подсолнечника - Рыбалко, Геннадий Кузьмич; Гончаренко, Борис Николаевич; Герман, Наталия Семеновна (My University, 1980)
Для проверки применимости СВЧ метода для определения влажности подсолнечника была изготовлена макетная установка, в которой использован принцип измерения затухания СВЧ колебаний при прохождении сквозь пробу семян в измерительном канале по сравнению с колебаниями в опорном канале. To test the applicability of the microwave method for determining moisture content of sunflower was made prototyping plant which uses the principle of measuring the attenuation of the microwave oscillations when passing through the sample in the measuring channel seeds compared with fluctuations in the reference channel.
Keywords: семена подсолнечника; влажность; измерения; точность; фактор; влияние; эксперимент; sunflower seeds; moisture; measurement; microwave engineering; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка